New genera, new species and new combinations for some African Coccomorpha (Hemiptera: Sternorrhyncha) - Hodgson, Chris J. (Zootaxa, 2021)
In the past, various authors have placed many species in genera that are now understood to be restricted to other regions of the world. Thus, in Africa, species of soft scale (Hemiptera: Sternorrhyncha: Coccomorpha: Coccidae) with this problem are those in Ceronema Maskell, a genus probably restricted to Australia; Ceroplastodes Cockerell, probably restricted to the New World; and Inglisia Maskell, which is restricted to New Zealand. The placement of these species is reviewed here. Four of the known Ceronema species are placed in three new monotypic genera, Neoceronema gen. nov., Illovococcus gen. nov. and Bugandacoccus gen. nov., as Neoceronema africanum (Macfie) comb. nov., N. brachystegiae (Hall) comb. nov., Illovococcus mobilis (Brain) comb. nov. and Bugandacoccus gowdeyi (Newstead) comb. nov.; Ceroplastodes ritchiei Laing and C. zavatarii Bellio are transferred to Drepanococcus Williams & Watson, as D. ritchiei (Laing) comb. nov. and D. zavattarii (Bellio), comb. nov., and Inglisia grevilliae Hall, I. pluvialis Hodgson and I. theobromae Newstead are transferred to Cryptinglisia Cockerell as C. grevilliae (Hall) comb. nov., C. pluvialis (Hodgson) comb. nov. and C. theobromae (Newstead) comb. nov. Keys are provided to all Drepanococcus and Cryptinglisia species, and all the African species discussed are illustrated. In addition, another new genus of African Coccidae is described, Testudovestis gen. nov., to take a new species somewhat similar to Eucalymnatus Cockerell: T. africana spec. nov. In addition, a new species of Coccus L.: Coccus moorei, spec. nov., and a new species of mealybug (Heliococcus tinglei spec. nov., Pseudococcidae), are described, both from mainland Africa. The lecanodiaspid Lecanodiaspis zygophylli Hodgson is also recorded from Nigeria for the first time.